2017
DOI: 10.1038/nrg.2017.74
|View full text |Cite
|
Sign up to set email alerts
|

Emerging and evolving concepts in gene essentiality

Abstract: Gene essentiality is a founding concept of genetics with important implications in both fundamental and applied research. Multiple screens have been performed over the years in bacteria, yeasts, animals and more recently in human cells to identify essential genes. A mounting body of evidence suggests that gene essentiality, rather than being a static and binary property, is both context dependent and evolvable in all kingdoms of life. This concept of a non-absolute nature of gene essentiality changes our funda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
265
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(276 citation statements)
references
References 209 publications
10
265
1
Order By: Relevance
“…The screen we performed spans over several time points, which allowed us to quantify the gRNA decline rate and cluster the essential genes into two groups. We found that genes in the fast declining group are more highly expressed, less likely to have a paralog and are enriched for fundamental cellular functions, all of which are general properties of essential genes (Rancati et al 2017;White et al 2013). While there is possibility that the genes in the fast-declining group are essential for survival whereas the genes in the gradual-declining group are essential for proliferation, our analysis implies that there is a quantitative difference in the level of essentiality between the gene groups.…”
Section: Discussionmentioning
confidence: 58%
“…The screen we performed spans over several time points, which allowed us to quantify the gRNA decline rate and cluster the essential genes into two groups. We found that genes in the fast declining group are more highly expressed, less likely to have a paralog and are enriched for fundamental cellular functions, all of which are general properties of essential genes (Rancati et al 2017;White et al 2013). While there is possibility that the genes in the fast-declining group are essential for survival whereas the genes in the gradual-declining group are essential for proliferation, our analysis implies that there is a quantitative difference in the level of essentiality between the gene groups.…”
Section: Discussionmentioning
confidence: 58%
“…In cancer therapeutics, following genetic alteration in a tumor suppressor gene, pharmacologic inhibition of compensatory mechanisms serves as an approach to selectively target malignant cells 1. The poly(ADP-ribose) polymerase (PARP) enzymes, including PARP1, PARP2, and PARP3, are essential to multiple DNA repair pathways and have been shown to have a potentially lethal interaction when inhibited in the presence of a mutation in BRCA1 or BRCA2 2 3.…”
Section: Introductionmentioning
confidence: 99%
“…Even when multiple large chromosomal regions can be removed, significant growth defects often result from accumulating losses of 'quasi-essential' genes, defined as genes that are not needed for survival but are required for robust growth (3,8,18,20,21). Given how difficult it is to predict how gene essentiality and quasi-essentiality generalizes across environments (22), it is often necessary to empirically test the viability and performance of many different deletions and combinations of those deletions to create a useful minimal genome organism.…”
Section: Introductionmentioning
confidence: 99%